Effect of peer education on knowledge and frequency of smoking among high school students in disadvantaged districts: a quasi-experimental study - Mermer, Gulengul; Nurcan Bilgic; Keskin, Salih; Gunay, Turkan (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the effectiveness of peer education on changing the knowledge and frequency of smoking of high school students. Method: The quasi-experimental study was conducted at the Vocational and Technical Anatolian High School, Turkey, during the 2021-22 academic year, and comprised students of either gender from the 9th to the 11th grade. After baseline assessment, training that blended peer education with the photovoice technique was administered between March 2021 and January 2022. Post-intervention assessment included smoking frequency, cigarette exposure and health literacy. Data was analysed using R version 4.0.5. Results: Of the 465 students available, 395(84.95%) were part of the baseline assessment, while 434(93.3%) took the post-intervention assessment. At the baseline, 365(93.8%) participants were males and 24(6.2%) were femaes. The overall median age was 15 years (interquartile range: 15-16 years). Post-training, smoking rate and indoor exposure to cigarette smoke among the students were statistically lower than the baseline values (p<0.05). The mean health literacy score post-intervention was significantly higher than the baseline score (p<0.05). Conclusion: Photovoice combined with peer education seemed beneficial in terms of positive effect on smoking behaviour among youths. Key Words: Peer education, Smoking cessation, Peer influence, Smoking prevention, Adolescent, Health literacy.